The Management of School Operational Assistance (SOA) through Tax Administration at Tojo Una Una’s Financial and Asset Management Agency - Muhammad Iqbal Bakri; Andi Mattulada; Muhammad Ikbal Abdullah; Fikry Karim; Abdul Kahar; Muliati; Muhammad Din; Femilia Zahra; Andi Chairil Furqan (Research Horizon, 2022)
School Operational Assistance (SOA) is a government program that provides funding for personnel operational costs for basic education units as implementing compulsory learning programs. This study aims to analyze the management of School Operational Assistance (SOA) through tax administration at Tojo Una Una’s Financial and Asset Management Agency, Central Sulawesi Province, Indonesia. The approach that will be taken in implementing community service activities is through an explanation of the management of the SOA fund treasurer and the person in charge of the principal of each school in the Tojo Una Una Regency, the duties and authorities of the SOA fund treasurer. Pre and post-tests were tested using the Compare Means Paired- Sample T-Test analysis with the statistical analysis tool SPSS because the data came from the same subject. The results highlight that the management of SOA funds has not been fully effective because several factors that lead to the achievement of the objectives of managing funds have not been achieved, including planning, implementation, and accountability aspects. Therefore, to improve technical capabilities and skills in the management of SOA funds, especially related to SOA tax administration, it is necessary to carry out service in the form of socialization related to SOA tax administration, which will be framed in an effective communicative, and relaxed manner.